MENCARI TEKS UNTUK PENERJEMAH PEMULA UNTUK BERLATIH MENERJEMAHKAN - Sunardi, FX Dono (Jurnal Penerjemahan, 2024)
This article explores the importance of identifying texts that help a beginner translator improve his/her skills through practice. First, it will define what a beginner translator is and, secondly, what characteristics a text should have to be used as a practice text. The study finds that a beginner translator, characterized by his/her lack of knowledge and skills in translating due to insufficient experience, often faces language and cultural challenges, leading to unnatural translations. To address these issues, practicing with well-suited texts is crucial. Using an online survey distributed to HPI (Association of Indonesian Translators) members, the article identifies five key text characteristics for beginners: grammatical accuracy, low complexity, minimal idiomatic and archaic language, relevance to the translator's field of study, and manageable length (150-200 words or 5-20 pages). To those findings, the study adds that a beginner translator should understand his/her own learning styles to optimize their practice and skill development.